Pengaruh Psychological Capital terhadap Work Engagement pada Crew Outlet - Salsabila Azzahra; Agus Budiman (UNISBA Press, 2022)
Abstract. The purpose of this study was to examine the effect of psychological capital on work engagement at crew outlet. Psychological capital is a positive psychological condition of individuals who have the characteristics of self-efficacy, optimism, hope and resilience (Luthans et.al 2007). Work engagement is a positive emotion and full involvement at work which is characterized by vigor, dedication, and absorption (Schaufeli et al., 2002). The method used is quantitative with multiple regression technique. The subjects of this study were 62 crew outlet employees calculated using the slovin formula from 157 crew outlet employees. Psychological capital measuring tools are PCQ-24 from Luthans et.al (2007) and work engagement using UWES-17 from Schaufeli & Bakker (2002). The results showed that psychological capital had a significant effect on work engagement by 75.3%. All dimensions of psychological capital have a significant effect on work engagement, especially Hope dimension with the largest influence and self-efficacy dimension with the least effect. Abstrak.: Tujuan dari penelitian ini adalah untuk menguji pengaruh psychological capital terhadap work engagement pada crew outlet. Psychological capital adalah kondisi psikologis yang bersifat positif dari individu yang memiliki karakteristik self-efficacy, optimisme, hope dan resilience (Luthans et.al 2007). Work engagement adalah emosi positif dan keterlibatan penuh ketika bekerja yang ditandai dengan vigor, dedication, dan absorption (Schaufel et al., 2002). Metode yang digunakan kuantitatif dengan teknik multiple regression. Subjek penelitian ini adalah 62 karyawan crew outlet yang dihitung menggunakan rumus slovin dari 157 karyawan crew outlet. Alat ukur psychological capital adalah PCQ-24 dari Luthans et.al (2007) dan work engagement menggunakan UWES-17 dari Schaufeli & Bakker (2002). Hasilpenelitian menunjukkan bahwa psychological capital memberikan pengaruh yang signifikan terhadap work engagement sebesar 75.3%. Seluruh dimensi psychological capital memiliki pengaruh yang signifikan terhadap work engagement terutama dimensi Hope dengan pengaruh paling besar dan dimensi self-efficacy dengan pengaruh paling kecil.